The balance between intestinal immune homeostasis and inflammation - Samsom, Janneke (Henry Stewart Talks, 2023)
Inflammatory bowel disease (IBD), Clinical subtypes of IBD, Ulcerative colitis, Crohn’s disease, Commensal and pathogenic bacteria in the intestinal mucosa, Role of innate and adaptive immunity in the intestine mucosa, Immune pathways involved in IBD, IBD susceptibility genes, Very early onset IBD (VEO-IBD)